Ecosystem-based adaptation: effect of shade trees on ecosystem services in coffee plantations - Villarreyna, Rogelio Antonio (2020)
Introduction. The management of shade trees in a production system is considered an ecosystem-based adaptation practice capable of providing multiple ecosystem services. Objective. Contribute to the understanding of the effects of trees in coffee plantations on ecosystem services for provisioning and regulation and how the analysis of relationships between services can contribute to improve the design and management of these systems. Development. The study was carried out between July and October 2017. Shade trees have an effect on coffee yield, attributed to their influence on the regulation of fruit load. This effect can have positive results with an adequate agroforestry management, as it would reduce extreme biennial fluctuations in coffee production. The trees also regulate the climate within the coffee plantation (microclimate), in addition, they have positive effects on soil fertility, the amount of organic matter, the recycling of nutrients, decrease soil evaporation, reduce erosion and sequester carbon. However, there are some aspects that are still complex and sometimes contradictory. Overall, the documentation of the positive aspects of the trees on provisioning and regulation services is greater than the negative ones. Conclusion. This review shows an effect of shade trees on ecosystem services. Knowledge of these effects, considering the interest and expectations of the social systems, must be complemented with analysis of relationships between services with the aim to identifying best agroforestry practices or model systems that can provide multiple services simultaneously.